1997
DOI: 10.1002/(sici)1097-0223(199705)17:5<435::aid-pd100>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Steroid 21-Hydroxylase Deficiency by Analysis of Polymerase Chain Reaction–single Strand Conformation Polymorphism (Pcr–sscp) Profiles

Abstract: The polymerase chain reaction–single strand conformation polymorphism (PCR–SSCP) profile analysis could be applied to the prenatal diagnosis of steroid 21‐hydroxylase deficiency. We designed PCR primers to amplify most of the 21‐hydroxylase gene, including all the mutations previously reported. PCR–SSCP analysis in eight patients showed at least one polymorphic site in each case. We confirmed that the mobility shifts in SSCP in an affected kindred were transmitted as a Mendelian trait. As these results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A quantitative PCR was developed for sex determination in fetal cells (226). PCR-single-strand conformation polymorphism was applied to the prenatal diagnosis of 21-hydroxylase deficiency (227). Metherell et al showed that microbial identification can be accomplished by PCR amplification of endonuclease class II target sequences (228).…”
Section: Amplification Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…A quantitative PCR was developed for sex determination in fetal cells (226). PCR-single-strand conformation polymorphism was applied to the prenatal diagnosis of 21-hydroxylase deficiency (227). Metherell et al showed that microbial identification can be accomplished by PCR amplification of endonuclease class II target sequences (228).…”
Section: Amplification Techniquesmentioning
confidence: 99%
“…A quantitative PCR was developed for sex determination in fetal cells (226). PCR-single-strand conformation polymorphism was applied to the prenatal diagnosis of 21hydroxylase deficiency (227). of 16S-rRNA by using an electrochemiluminescence hybridization assay (229).…”
Section: Amplification Techniquesmentioning
confidence: 99%